Four Agricultural Financing Scenarios for Sub-Saharan Africa toward 2055: Conditions for Governmental Policy Interventions. (September 2019) - Oberholster, Cobus; Adendorff, Chris
This article reports on a research effort that looked at the future of agricultural financing in Sub-Saharan Africa, and provides governments in the region with key insights into agricultural development and the rural agricultural financing challenges. In the process of knowledge creation, a mixed-method approach was followed, with the futures triangle, emerging issues analysis, and causal layered analysis (CLA) being used to deepen the level of understanding regarding the future of agricultural financing. In addition, a real-time Delphi study was conducted to validate and prioritize the emerging trends and driving forces, and to incorporate expert knowledge into the possible financing futures. Four scenarios are presented that aim to stimulate new thoughts on policies that can facilitate increased financial inclusion in agricultural development in Sub-Saharan Africa.